The impact of divorce on children and sibling relationships in Malay community and policy responses / Ria Wardiah Azmi - Azmi, Ria Wardiah (2015)
This research examines the impact of divorce on children and sibling relationships and policy responses. Numerous researchers and scholars have articulated the needs for more research on the issue. Despite the significantly increasing number of divorce cases happen every day in the society, very limited research have been conducted especially in Malaysia. In this qualitative study, ten underage respondents share their experience about the impact of their parent’s divorce on themselves and their sibling’s relationship. As a result of the study, the impact of divorce on children has been identified. This includes the impact on children’s feeling; physical impact; social impact; and the impact on education. The findings also indicate positive and also negative impact of divorce on sibling relationships before and after the divorce took place. On other note, the study also briefly analyse the policy responses by the government on this issue. This study focus on the counselling programs conducted by JAIS and examines the awareness of the children of divorced family about the program.